A. C. Mukerji on the Problem of Skepticism and Its Resolution in Neo-Vedānta - Garfield, Jay L. (International journal for the study of skepticism, 2022)
This paper examines the work of the unsung modern Indian Philosopher A. C. Mukerji, in his major works Self, Thought and Reality (1933) and The Nature of Self (1938). Mukerji constructs a skeptical challenge that emerges from the union of ideas drawn from early modern Europe, neo-Hegelian philosophy, and classical Buddhism and Vedānta. Mukerji’s worries about skepticism are important in part because they illustrate many of the creative tensions within the modern, synthetic period of Indian philosophy, and in part because they are truly profound, anticipating in interesting ways the worries that Feyerabend was to raise a few decades later. Arguing that Humean, Kantian, neo-Hegelian, and Buddhist philosophy each fail to provide an adequate account of self-knowledge, Mukerji leverages this finding to further argue that these systems fail to offer a proper account of knowledge more generally. His solution to skepticism centers on a distinctively modern interpretation of Śaṅkara’s Vedānta.